Effect of Topical Latanoprost 0.005% Drops on Central Corneal Thickness in Patients with Primary Open Angle Glaucoma - , Farooq Khan, Awais Rauf, Akhunzada Mohammad Aftab, Mubashir Rehman, Sher Akbar Khan (Pakistan Journal of Ophthalmology, 2015)
Purpose: To determine the effect of topical 0.005% Latanoprost on central corneal thickness in patients with Primary Open Angle Glaucoma. Material and Methods: This study was conducted at Eye “A” unit, Khyber Teaching Hospital, Peshawar. Total sample size was 139 eyes. Baseline IOP measurement was taken with Goldman applanation tonometer. Central corneal thickness was measured by a single trained doctor using the Quantel® Pachymeter. All patients were prescribed Latanoprost 0.005% eye drops once daily in the evening. Follow up was at 2 weeks and 8 weeks. Results: Mean age was 52 years with SD ±2.71. Sixty nine (55%) patients were male and 56 (45%) were female. Mean difference between baseline CCT and CCT after eight weeks was 4% as mean baseline CCT level was 538 ?m with SD ± 1.87 and mean CCT level after 8 weeks was 534 ?mwith SD ±2.12. Efficacy of effect of Latanoprost on central corneal thickness of patients with primary open angle glaucoma was analyzed as Latanoprost was effective in reducing CCT in 104 eyes (75%) of 94 patients and was not effective in 35 eyes (25%) of 31 patients. Conclusion: Our study concludes that topical 0.005% Latanoprost eye drops reduces the central corneal thickness, so latanoprost therapy requires careful monitoring while treating patients with primary open angle glaucoma. However this reduction in CCT was not ? 25 µm from base line reading which is not significant enough and hence did not have an effect on IOP reading using Goldman applanation tonometer. Key words: Latanoprost, central corneal thickness, Primary Open Angle Glaucoma.